Fluid power with applications - Esposito, Anthony, 1934- (Upper Saddle River, N.J. : Pearson Prentice Hall, 2009)
Fluid Power with Applications, Seventh Edition presents broad coverage of fluid power technology in a readable and understandable fashion. An extensive array of industrial applications is provided to motivate and stimulate students' interest in the field. Balancing theory and applications, this book is updated to reflect current technology; it focuses on the design, analysis, operation, and maintenance of fluid power systems. It also includes an Automation Studio CD (produced by Famic Technologies Inc.) that contains simulations and animations of many of the fluid power circuits presented throughout the book as well as a variety of additional fluid power applications.
Introduction to fluid power -- Physical properties of hydraulic fluids -- Energy and power in hydraulic systems -- Frictional losses in hydraulic pipelines -- Hydraulic pumps -- Hydraulic cylinders and cushioning devices -- Hydraulic motors -- Hydraulic valves -- Hydraulic circuit design and analysis -- Hydraulic conductors and fittings -- Ancillary hydraulic devices -- Maintenance of hydraulic systems -- Pneumatics : air preparation and components -- Pneumatics : circuits and applications -- Basic electrical controls for fluid power circuits -- Fluid logic control systems -- Advanced electrical controls for fluid power systems.
Includes index.
Keywords: Fluid power technology